Eksplorasi Jamur Makroskopis di Perkebunan Kelapa Sawit - Reny Dwi Riastuti; Ivoni Susanti; Dina Rahmawati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2018)
The aim of the research was to find out the kinds of macroscopic fungi at oil palm plantations in Rejosari village Megang Sakti subdistrict. The method of the research was qualitative-descriptive. The sampling technique was purposive sampling with exploration method. The result showed that there were 41 kinds of fungi. 38 kinds included in 8 ordo, 17 famili, 32 genus and 3 unidentified macroscopic fungi. The observation results of abiotic environment of macroscopic fungi at oil palm plantations in Rejosari such as the air temperature was between 25-33 C, the air humidity was between 50-97%, the soil humidity was between 40-90%, and the scale of acidity (pH) was between 6,5-7,5. In conclusion, at the three locations, it was found that there were the consumable fungi, non-consumable fungi and medicinal fungi. Keywords: stocktaking, macroscopic fungi, oil palm plantations